2009
DOI: 10.1063/1.3177067
|View full text |Cite|
|
Sign up to set email alerts
|

Broadband electromagnetic-wave absorption by FeCo/C nanocapsules

et al.

Abstract: Electromagnetic-wave absorption by FeCo/C nanocapsules has been investigated. In contrast to earlier reported materials, including other nanocapsules, the absorption amplitude of FeCo/C nanocapsules is found not to decrease with increasing absorption-layer thickness. A reflection loss ͑RL͒ exceeding Ϫ20 dB can be obtained for all frequencies within the 2-18 GHz range by choosing an appropriate layer thickness between 1.6 and 8.5 mm. The broadest bandwidth ͑RL values exceeding Ϫ10 dB͒ from 10 to 18 GHz, coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
99
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 19 publications
7
99
1
Order By: Relevance
“…[ 3,[6][7][8][9][10] FeCo/graphitic carbon (FeCo/GC) core-shell nanoparticles have been suggested as a promising material for multipurpose diagnosis and therapeutic applications such as magnetic resonance imaging (MRI), near-infrared (NIR) photothermal therapy, and drug delivery [ 11 ] owing to their combination of a highly magnetic metal core and a graphitic carbon shell with a suitable absorbance of near-infrared (NIR) light and capability of loading drugs (i.e., doxorubicin (DOX)) through π -stacking. They have been also used for other applications including electromagnetic (EM)-wave absorption [ 12 ] and as a support for acid catalysts. [ 13 ] FeCo nanoparticles with graphitic shells have been fabricated through various methods including methane chemical vapor deposition, [ 3 ] radio-frequency plasma torch, [ 4 ] thermal conversion of Prussian blue analogues, [ 6 ] and an arc-discharge process, [ 12,14 ] but a scalable, effi cient, and controllable method for coating metal nanoparticles with a high-quality graphitic shell has thus far been elusive.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,[6][7][8][9][10] FeCo/graphitic carbon (FeCo/GC) core-shell nanoparticles have been suggested as a promising material for multipurpose diagnosis and therapeutic applications such as magnetic resonance imaging (MRI), near-infrared (NIR) photothermal therapy, and drug delivery [ 11 ] owing to their combination of a highly magnetic metal core and a graphitic carbon shell with a suitable absorbance of near-infrared (NIR) light and capability of loading drugs (i.e., doxorubicin (DOX)) through π -stacking. They have been also used for other applications including electromagnetic (EM)-wave absorption [ 12 ] and as a support for acid catalysts. [ 13 ] FeCo nanoparticles with graphitic shells have been fabricated through various methods including methane chemical vapor deposition, [ 3 ] radio-frequency plasma torch, [ 4 ] thermal conversion of Prussian blue analogues, [ 6 ] and an arc-discharge process, [ 12,14 ] but a scalable, effi cient, and controllable method for coating metal nanoparticles with a high-quality graphitic shell has thus far been elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric and magnetic loss tangents values are found to have opposite trend with frequency. Han et al [26] has also reported a quite similar loss spectrum for FeCo/C nanocapsules based system. They speculated the enhancement of absorption results from an excellent synergistic effect of magnetic and dielectric losses of the material.…”
Section: Resultsmentioning
confidence: 60%
“…As shown in Figure 3b, for all frequencies within the 1-18 GHz range, RL values exceeding -20 dB can be obtained by selecting an appropriate thickness of the absorbent layer between 1.1 and 10.0 mm. Compared with other carboncoated nanoparticles or nanowires (e.g., Sn/C [3] , Ni/C [28] , FeNi/C [10] , FeCo/C [29] , and FeCoNi/carbon nanotubes [30] ), the non-magnetic carbon-coated Cu nanocapsules present quite different and excellent EM-wave absorption properties, which may be due to the special microstructure of the Cu nanocapsules, the size of the Cu nanocapsules, and also the weight fraction of paraffin-Cu nanocapsules composite 3 . Generally, there are two mechanisms of energy attenuation in materials: magnetic loss and dielectric loss 3 .…”
Section: As Shown Inmentioning
confidence: 99%